Mass transfer at the electrode tip during gas metal arc welding - Portillo López, Dimas Eloy, (The University of Texas, 1995)
The main objective of this investigation is to study the evolution of a drop of molten metal from the electrode tip during Gas Metal Arc Welding (GMAW) for different welding conditions. These welding conditions are characterized by the current density distribution at the free surface of the pendant drop, the electric current level, the electrode feed velocity, and the surface tension coefficient. The drop diameter, average drop velocity, and evolution time are calculated for different combinations of the former parameters and compared with predicted values from the static force balance theory, the pinch instability theory, and experimental results. The mixed, velocity-pressure, Galerkin finite element method is used to solve the time dependent system of nonlinear governing equations. A Lagrangian-Eulerian formulation of the system of equations is required to account for the continuous deformation of the liquid domain. Grid nodes at the free surface of the drop are constrained to move normal to this interface. Also, no fluid is allowed to cross the free surface since evaporation has been neglected. Although the energy equation is presented here for completeness, it is not solved in order to reduce the complexity of the computer program. Therefore, material properties are evaluated at a representative reference temperature level. The results of this research will help to demonstrate the welding parameters which have a greater effect upon the size and dynamic characteristics of the detaching drops. The results of this mathematical model show that the current density distribution plays a major role in determining the size of the drops detaching from the electrode tip. Meanwhile, the electric current level and the surface tension coefficient have more influence in the velocity and evolution time of the drops.